Math, asked by yashj9902, 4 months ago

The differential equation
(3x + 2)2 dmx + 3(3x + 2)(x - 36y = { [(3x + 2)2 – 1) on putting
(3x + 2) = ex and using D
---
d
is transformed into
dz
A) (D2 + 3D – 36)y = z; (e22 - 1)
C) (D2 – 4)y = (C22 – 1)
B)(D2 + 4)y = -(e22 - 1)
D) (D2 - 9y = (e22 - 1)
ОА
OB
Ос
OD
100%​

Answers

Answered by parasmalkhatri9
0

Step-by-step explanation:

brainly.in › Math › Secondary School

Web results

The differential equation(3x + 2)2 dmx + 3(3x + 2)(x - 36y = { [(3x + 2 ...

Similar questions